Bio-resin production through ethylene unsaturated carbon using vegetable oils - Ab. Latif, Farah Ezzah; Zainal Abidin, Zurina; Cardona, Francisco; Awang Biak, Dayang Radiah; Abdan, Khalina; Md. Tahir, Paridah; Liew, Kan Ern (MDPI, 2020)
Bio-resins are bio-based materials derived from vegetable resources, especially from vegetable seed oils. It is widely known that bio-resources are renewable, highly available, and sustainable. Resins and most polymers are largely derived from petroleum-based sources that are known to pose chemical risks. Resins have practical applications in printing inks, plasticisers and diluents, as well as in coating materials. Vegetable oils possess a large number of oxirane groups, which are essential for epoxidation to occur, resulting in the production of bio-resins. This undeniably serves as a promising candidate for competing with fossil-fuel-derived petroleum-based products. Thus, the aim of this review paper is to highlight aspects related to the production of bio-resins, including the chemical route of vegetable oil epoxidation process and its influencing factors, the reaction kinetics, bio-resins and the physico-chemical and mechanical properties of bio-resins, along with their applications. The resins industry has seen some remarkable progress towards the commercialisation of several bio-resins originating from vegetable oils, such as soybean oil, castor oil, and linseed oil. This success has undoubtedly intensified further efforts in fields related to bio-resin applications. Research and development is ongoing with the aim of customising a feasible formulation for the synthesis of bio-resins with the desired properties for catering to various applications.